Fetal Urinoma Due to Circulatory Disorders in an Umbilical Artery: Case Report. (August 2021) - Kozlova, Daria; Gilboa, Yinon; Sade-Zalts, Chen; Gielchinsky, Yuval; Shteingart, Shimon; Kidron, Debora
Fetal urinoma is defined as an encapsulated accumulation of extravasated urine within the perirenal space or retroperitoneum. It is an uncommon finding in prenatal practice, and the vast majority of known cases are strongly associated with the existence of a urinary obstruction, such as posterior urethral valves, ureteropelvic junction obstruction, or ureterocele. We report a unique case of prenatally detected fetal bladder urinoma that occurred in the absence of an apparent obstructive uropathy, but was associated with extensive ischemic necrosis and calcifications of adjacent bladder wall, coexistent with signs of vascular supply decompensation.